Mothers at peace: Post-conflict fertility and United Nations peacekeeping - Vincenzo Bove; Jessica Di Salvatore; Leandro Elia; Roberto Nisticò (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Armed conflict can shape reproductive behaviour as high child mortality and a lack of health services lead to higher fertility rates. Yet women often postpone childbearing in expectation of better times. Given the theoretical ambiguity, the extant empirical evidence is often inconclusive. As a lack of security is a key factor in shaping these decisions, we investigate whether the deployment of United Nations peacekeepers affects fertility in post-conflict settings. We study the case of Liberia from 2003 to 2019 by combining data on birth histories from three rounds of the Demographic and Health Survey with geocoded information on the distance to United Nations bases. We find that women who live in the proximity of peacekeepers have lower fertility rates in the deployment period. Furthermore, peacekeeping improves child health and fosters family planning, as parents prioritize 'quality' over 'quantity'.
Keywords: J13; D74; F53; 330; fertility; conflict; UN peacekeeping